Cytomegalovirus and Epstein-Barr virus infections among Jordanians: seroprevalence and associated factors - Hassan M. Kofahi; Samer F. Swedan; Maen Aljezawi (BMC Infectious Diseases)
Abstract Background Cytomegalovirus (CMV) and Epstein-Barr virus (EBV) are widespread infections, with seroprevalence rates varying by region and demographic characteristics. This study aimed to examine the seroprevalence of EBV and CMV in the Jordanian population and explore possible risk factors associated with these infections. Methods A total of 1,507 individuals were recruited through convenience sampling from hospitals located in the central and northern regions of Jordan. Participants were stratified by age, sex, and geographic area. Blood samples were analyzed for EBV-VCA and CMV IgG antibodies using ELISA. Demographic and socioeconomic information was also collected. To identify potential risk factors, multivariate logistic regression was conducted, focusing on variables such as age, sex, marital status, education level, monthly income, region, and type of residence. Results The overall seroprevalence was 88.7% for CMV-IgG and 91.0% for EBV-IgG. The seroprevalence of both CMV and EBV increased with age from 62.4% and 70.6%, respectively, in children under five years of age to 100.0% and 96.5% in participants aged 60 years and above. Regression analysis indicated that older age and being ever married (i.e., married, divorced, or widowed) were significantly associated with higher seroprevalence of both viruses. Additionally, having a monthly income of 64.3 JD or more per individual was independently linked to lower EBV seroprevalence. Conclusion EBV and CMV seroprevalence in Jordan was remarkably high. Age was the most prominent risk factor, with marital status and income contributing as independent predictors. These findings offer a valuable reference point for future public health efforts, including surveillance and vaccination strategies targeting high-risk groups.